2022
DOI: 10.53992/njns.v7i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morinda Citrifolia Linn (Noni) and Tahitian Noni® Juice (Tnj) on Locomotor Activity in Mice

Abstract: Noni fruit extract and juice (Morinda citrifolia L., Family: Rubiaceae) had long been known as a medicinal plant in folklore medicine in tropical countries and Pacific islands. To date, the available scientific knowledge was focused on different pharmacological effects. It was claimed to have a beneficial effect on drug addiction by Noni fruit extract and its juice in animal studies. Keeping this in mind we investigated whether the noni fruit extract and noni beverages contained any effect on locomotion in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Researchers have suggested that these effects may be linked to the activation of central opioid receptors. These findings suggested that M. citrifolia extract and Tahitian noni juice are safe and can be used for further neuropharmacological research, as mentioned by Khan et al in 2022 [ 72 ].…”
Section: Resultsmentioning
confidence: 72%
“…Researchers have suggested that these effects may be linked to the activation of central opioid receptors. These findings suggested that M. citrifolia extract and Tahitian noni juice are safe and can be used for further neuropharmacological research, as mentioned by Khan et al in 2022 [ 72 ].…”
Section: Resultsmentioning
confidence: 72%